Functional Analysis Reveals Geographical Variation in Inhibitory Immune Responses Against a Polymorphic Malaria Antigen. (9th June 2017) - Bei, Amy K; Ahouidi, Ambroise D; Dvorin, Jeffrey D; Miura, Kazutoyo; Diouf, Ababacar; Ndiaye, Daouda; Premji, Zul; Diakite, Mahamadou; Mboup, Souleymane; Long, Carole A; Duraisingh, Manoj T
Summary: Transgenic parasites harboring a naturally-arising polymorphism in PfRh2b reveal no invasion pathway difference but are differentially inhibited by IgG from three endemic regions. Transgenic parasites provide a useful tool to assess specificity of natural or vaccine-induced inhibitory antibodies. Abstract: Background: Plasmodium falciparum reticulocyte-binding protein homologue 2b (PfRh2b) is an invasion ligand that is a potential blood-stage vaccine candidate antigen; however, a naturally occurring deletion within an immunogenic domain is present at high frequencies in Africa and has been associated with alternative invasion pathway usage. Standardized tools that provide antigenic specificity in in vitro assays are needed to functionally assess the neutralizing potential of humoral responses against malaria vaccine candidate antigens. Methods: Transgenic parasite lines were generated to express the PfRh2b deletion. Total immunoglobulin G (IgG) from individuals residing in malaria-endemic regions in Tanzania, Senegal, and Mali were used in growth inhibition assays with transgenic parasite lines. Results: While the PfRh2b deletion transgenic line showed no change in invasion pathway utilization compared to the wild-type in the absence of specific antibodies, it outgrew wild-type controls in competitive growth experiments. Inhibition differences with total IgG were observed in the different endemic sites, ranging from allele-specific inhibition to allele-independent inhibitory immune responses. Conclusions: The PfRh2b deletion may allow the parasite to escape neutralizing antibody responses in some regions. This difference in geographical inhibition was revealed using transgenic methodologies, which provide valuable tools for functionally assessing neutralizing antibodies against vaccine-candidate antigens in regions with varying malaria endemicity.